Single phase transformerless inverter topologies for grid-tied photovoltaic system: A review. (May 2015) - Islam, Monirul; Mekhilef, Saad; Hasan, Mahamudul
Abstract: Grid-tied inverters are the key components of distributed generation system because of their function as an effective interface between renewable energy sources and utility. Recently, there has been an increasing interest in the use of transformerless inverter for low-voltage single-phase grid-tied photovoltaic (PV) system due to higher efficiency, lower cost, smaller size and weight when compared to the ones with transformer. However, the leakage current issues of transformerless inverter, which depends on the topology structure and modulation scheme, have to be addressed very carefully. This review focuses on the transformerless topologies, which are classified into three basic groups based on the decoupling method and leakage current characteristics. Different topologies under the three classes are presented, compared and evaluated based on leakage current, component ratings, advantages, and disadvantages. An examination of demand for the inverter, the utility grid, and the PV module are presented. A performance comparison in MATLAB/Simulink environment is done among different topologies. Also an analysis has been presented to select a better topology. Finally, based on the analysis and simulation results, a comparison table has been presented. Furthermore, some important experimental parameters have been summarized.